A CFD analysis of different human breathing models and its influence on spatial distribution of indoor air parameters - Bulińska, Anna; Buliński, Zbigniew (Computer Assisted Methods in Engineering and Science, 2017)
The computational fluid dynamics (CFD) analysis of the indoor environment in buildings requires numerical modelling of a human being (computer simulated person - CSP). There are two crucial aspects in developing reliable CSP models: the CSP geometry and the breathing model. This paper focuses on the analysis of different breathing models for application in the CFD modelling. Three breathing models were analysed: first model was restricted to constant exhalation, second model, the so-called full breathing, included constant rate inhalation, constant rate exhalation and pause period, and in the third model temporal variation of flow rate was represented by sinusoidal function. The main findings from this work show that all three models compared with experimental data gave reliable results. The spatial distribution of CO 2 concentration and velocity showed only small differences among the models in the vicinity of the mouth and above the person. It was shown that a simplified constant exhalation model can be effectively used for the CFD analysis of the indoor air quality (IAQ). However, a detailed simulation of micro-environment in the room and transport of contaminants should include complete breathing.